THE ROLE OF EDUCATIONAL PSYCHOLOGY IN ADDRESSING MENTAL HEALTH CHALLENGES IN EDUCATION - Yusuf, Achmad (MSJ : Majority Science Journal, 2025)
This study aims to describe the role of educational psychology in addressing mental health challenges in education and to identify intervention strategies implemented by teachers, counselors, and educational psychologists to support students' psychological well-being. The research method used was qualitative with a phenomenological approach. Data were obtained through in-depth interviews, observations, and documentation studies with informants consisting of teachers, school counselors, educational psychologists, and students. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions using thematic analysis techniques. The results of the study indicate that educational psychology plays a crucial role in early detection of mental health problems, providing interventions in the form of counseling and mentoring, and creating a more psychologically friendly school climate. The main obstacles in the application of educational psychology are limited counselor staff, minimal teacher training, and stigma regarding mental health issues. Nevertheless, the application of educational psychology principles has been shown to have a positive impact on learning motivation, emotional regulation, and the creation of a psychologically healthy learning environment.